Research on the metabolic regulation mechanism of Yangyin Qingfei decoction plus in severe pneumonia caused by Mycoplasma pneumoniae in mice - Zhang, Tianyu; Zhao, Xiyu; Zhang, Xining; Liang, Xiangyu; Guan, Zhenglong; Wang, Guanghan; Liu, Guanghua; Wu, Zhenqi (Frontiers in Pharmacology, 2024)
Aim of the study: This study examines the impact of Yangyin Qingfei Decoction (YQDP) on lung tissue metabolic products in severe Mycoplasma pneumoniae pneumonia (SMPP) model mice and examines the mechanism of YQDP in treating MP infection using UPLC-MS/MS technology.Materials and Methods: YQDP's chemical composition was ascertained by the use of Agilent 1260 Ⅱ high-performance liquid chromatography. By using a nasal drip of 10 10 CCU/mL MP bacterial solution, an SMPP mouse model was created. The lung index, pathology and ultrastructural observation of lung tissue were utilized to assess the therapeutic effect of YQDP in SMPP mice. Lung tissue metabolites were found in the normal group, model group, and YQDP group using UPLC-MS/MS technology. Using an enzyme-linked immunosorbent test (ELISA), the amount of serum inflammatory factors, such as interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α), was found. Additionally, the protein expression of PI3K, P-PI3K, AKT, P-AKT, NF-κB, and P-NF-κB was found using Western Blot.The contents of chlorogenic acid, paeoniflorin, forsythrin A, forsythrin, and paeonol in YQDP were 3.480 ± 0.051, 3.255 ± 0.040, 3.612 ± 0.017, 1.757 ± 0.031, and 1.080 ± 0.007 mg/g respectively. YQDP can considerably lower the SMPP mice's lung index. In the lung tissue of YQDP groups, there has been a decrease in the infiltration of inflammatory cells at varying concentrations in the alveoli compared with the model group. A total of 47 distinct metabolites, including choline phosphate, glutamyl lysine, L-tyrosine, 6-thioinosine, Glu Trp, 5hydroxydecanoate, etc., were linked to the regulation of YQDP, according to metabolomics study. By controlling the metabolism of porphyrins, pyrimidines, cholines, fatty acids, sphingolipids, glycerophospholipids, ferroptosis, steroid hormone biosynthesis, and unsaturated fatty acid biosynthesis, enrichment analysis suggested that YQDP may be used to treat SMPP. YQDP can lower the amount of TNF-α and IL-6 in model group mice as well as downregulate P-PI3K, P-AKT, and P-NF-κB expression. Conclusions: A specific intervention effect of YQDP is observed in SMPP model mice. Through the PI3K/Akt/NF-κB signaling pathways, YQDP may have therapeutic benefits by regulating the body's metabolism of α-Linoleic acid, sphingolipids, glycerophospholipids, arachidonic acid, and the production of unsaturated fatty acids.